2007
DOI: 10.1158/0008-5472.can-06-4126
|View full text |Cite
|
Sign up to set email alerts
|

The Telomerase Reverse Transcriptase (hTERT) Gene Is a Direct Target of the Histone Methyltransferase SMYD3

Abstract: Recent evidence has accumulated that the dynamic histone methylation mediated by histone methyltransferases and demethylases plays key roles in regulation of chromatin structure and transcription. In the present study, we show that SET and MYND domain-containing protein 3 (SMYD3), a histone methyltransferase implicated in oncogenesis, directly trans-activates the telomerase reverse transcriptase (hTERT) gene that is essential for cellular immortalization and transformation. SMYD3 occupies its binding motifs on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
95
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(97 citation statements)
references
References 34 publications
1
95
0
Order By: Relevance
“…And suppression of hTERT expression also results in elevated p53 and p21 transcription [78]. (c) The histone methyltransferase (SMYD3) implicated in oncogenesis directly transactivates the hTERT promoter and is required for inducible and constitutive hTERT expression in normal and malignant human cells [79]. On the other hand, it has been shown that expression of hTERT up-regulated transcription and promoter activity of DNA 5-methylcytosine transferase I gene (DNMT1) in normal human fibroblasts [73], although the mechanism by which hTERT-induced DNMT1 expression has yet to be determined.…”
Section: Telomerase In the Regulation Of Gene Expressionmentioning
confidence: 99%
“…And suppression of hTERT expression also results in elevated p53 and p21 transcription [78]. (c) The histone methyltransferase (SMYD3) implicated in oncogenesis directly transactivates the hTERT promoter and is required for inducible and constitutive hTERT expression in normal and malignant human cells [79]. On the other hand, it has been shown that expression of hTERT up-regulated transcription and promoter activity of DNA 5-methylcytosine transferase I gene (DNMT1) in normal human fibroblasts [73], although the mechanism by which hTERT-induced DNMT1 expression has yet to be determined.…”
Section: Telomerase In the Regulation Of Gene Expressionmentioning
confidence: 99%
“…SMYD3 methylates both H3K4 and H4K5 (Hamamoto et al 2004, Van Aller et al 2012, recruits RNA polymerase II through an RNA helicase to form a transcription complex, and elicits its oncogenic effects by activating the transcription of downstream target genes (Hamamoto et al 2004, 2006, Liu et al 2007. SMYD3 is also involved in apoptosis and the inhibition of cell growth, migration, and invasion (Xu et al 2006, Zou et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…SMYD3 has been reported to be capable of methylating both H3K4 and H4K5 (Hamamoto et al 2004, Van Aller et al 2012. Evidence has accumulated that suggests that SMYD3 recruits RNA polymerase II through an RNA helicase to form a transcription complex and that it elicits its oncogenic effects by activating the transcription of downstream target genes (Hamamoto et al 2004, 2006, Liu et al 2007. Previous reports have demonstrated that enhanced expression of SMYD3 is essential for the growth of human cancer cells (Hamamoto et al 2004(Hamamoto et al , 2006, whereas the suppression of SMYD3 expression leads to apoptosis and the inhibition of cell growth, migration, and invasion (Chen et al 2007, Zou et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…ChIP assay was carried out as described previously (44,45). The cells with different treatments were cross-linked by incubating them in 1% (vol/vol) formaldehyde-containing medium for 10 min at 37jC and then sonicated to make soluble chromatin with DNA fragments between 200 and 1,000 bp.…”
Section: Chipmentioning
confidence: 99%
“…44, 45): 5 ¶-CCAGGCCGGGCTCCCAGTG-GAT-3 ¶ (forward) and 5 ¶-GGCTTCCCACGTGCGCAGCAG-GA-3 ¶ (reverse); and upstream (hTERT-b) regions: 5 ¶-TCCCC-TTCACGTCCGGCATT-3 ¶ (forward) and 5 ¶-CGTCT-GTGCCCGCGAATCCA-3 ¶ (reverse). The primers for glyceraldehyde-3-phosphate dehydrogenase were described elsewhere (44,45).…”
Section: Chipmentioning
confidence: 99%